Self- Spirituality and its Advantageous Impact for Positive Counselling Attitudes among Youths - Tanimoonwo, Idowu Grace; Aishah, Hassan, Siti; Hamzah, Azimi; Maznah, Baba (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
This paper presents the influences of self-spirituality for prosperous Counselling attitudes among youths with particular focusÂ on Nigerian students in Malaysian Universities, towards becoming positive agents of change in the society. The researchÂ paper analyses ways in which self-spirituality can be applied independently as a Counselling means to achieve positiveÂ attitudes among these university students. The Null hypothesis stated that there are no significant and direct relationshipsÂ between self-spirituality and counselling attitudes. To carry out the research, two instruments were combined in aÂ quantitative survey involving 394 students that were systematically drawn from ten randomly selected universities inÂ Malaysia. The results of the data analysis indicate the fact that self-spirituality has a positive impact on counselling attitudes with (Î² =0.212 and p value = 0.002). The null hypothesis was therefore rejected. The analysis ends with a discussion thatÂ provides recommendations that can be adopted to ensure success of the self-spirituality use in counselling. The paperÂ suggested with remarkable conclusion that since spirituality plays such an important role in every society, there should be more nurturing of it in the society while the Guidance Counsellors work towards directing the young people on the right pathÂ of God.